Proses Belajar Mengajar Melalui Interaksi Edukatif Berdasarkan Surah al-Kahfi ayat 66 sampai 78 - subhani, niimma; Charles, Charles; Wardani, Febri (Universitas Muhammadiyah Tangerang, 2024)
The teaching and learning process between Prophet Khidir and Prophet Moses in the context of educational interaction is an example that is rich in educational values in Islam. This story, listed in the Qur'an surah al kahf verses 66 to 78 which describes the journey of Prophet Moses who wants to learn from Prophet Khidir, a person who has knowledge that he does not have. This study aims to analyze the aspects of educational interaction that occurred between the two prophets, including the principles of learning, the manners of teachers and students. Through a qualitative approach and text analysis, this study found that the interaction between Khidir and Moses reflected the importance of discipline, patience, and mutual respect in the educational process. In addition, the lesson given by Prophet Khidir to Prophet Moses shows a contextual and gradual learning method, where every action has deep wisdom. The results of this study are expected to provide new insights into the concept of education in Islam and its application in the modern context.